Evaluation of size distribution of starch granules in selected wheat varieties by the Low Angle Laser Light Scattering method - I. Capouchová; J. Petr; D. Marešová (Plant, Soil and Environment, 2003)
The distribution of the size of wheat starch granules using the method LALLS (Low Angle Laser Light Scattering), followed by the evaluation of the effect of variety, experimental site and intensity of cultivation on the vol. % of the starch A (starch granules > 10 μm) was determined. The total starch content and crude protein content in dry matter of flour T530 in selected collection of five winter wheat varieties were determined. Vol. % of the starch A in evaluated collection of wheat varieties varied between 65.31 and 72.34%. The effect of a variety on the vol. % of starch A seemed to be more marked than the effect of site and intensity of cultivation. The highest vol. % of starch A reached evaluated varieties from the quality group C, i.e. varieties unsuitable for baking utilisation (except variety Contra with high total content of starch in dry matter of flour T530, but relatively low vol. % of starch A). A low vol. % of starch A was also found in the variety Hana (very good variety for baking utilisation). Certain variety differences followed from the evaluation of distribution of starch fractions of starch granules, forming starch A. In the case of varieties Hana, Contra and Siria higher representation of fractions up to 30 μm was recorded, while starch A in the varieties Estica andVersailleswas formed in higher degree by size fractions of starch granules over 30 μm and particularly size fraction > 50 μm was greatest in these varieties of all evaluated samples. With increasing total starch content in dry matter of flour T530 the crude protein content decreased; the vol. % of starch A not always increased proportionally with increasing total starch content.